2013
DOI: 10.1186/1472-6963-13-328
|View full text |Cite
|
Sign up to set email alerts
|

Can a theory-based educational intervention change nurses’ knowledge and attitudes concerning cancer pain management? A quasi-experimental design

Abstract: BackgroundRegistered Nurses (RNs) play an important role in caring for patients suffering from cancer pain. A lack of knowledge regarding pain management and the RNs’ own perception of cancer pain could act as barriers to effective pain management. Educational interventions that target RNs’ knowledge and attitudes have proved promising. However, an intervention consisting of evidence-based practice is a multifaceted process and demands behavioural and cognitive changes to sustain the effects of the interventio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 48 publications
0
21
0
1
Order By: Relevance
“…Therefore, it is necessary to expand the role of nurses to overcome the obstacles for managing pain in clinical practice [5]. Insufficient knowledge and the prejudice of nurses on cancer pain could be an obstacle to an effective pain management [12]. Only 20∼30% of health care workers received education of cancer pain management.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is necessary to expand the role of nurses to overcome the obstacles for managing pain in clinical practice [5]. Insufficient knowledge and the prejudice of nurses on cancer pain could be an obstacle to an effective pain management [12]. Only 20∼30% of health care workers received education of cancer pain management.…”
Section: Introductionmentioning
confidence: 99%
“…Results of health education for nurses showed that the professionals who participated in the programs reported greater confidence to assess the pain, to have a more effective attitude to management this symptom, and they also reported reduction of barriers [17][18][19]. As an effective result, higher patient satisfaction was obtained, which was caused by two aspects.…”
mentioning
confidence: 84%
“…Among the interventions that were made in the studies, 5 (26.3%) evaluated Educational Programs, which include the implementation of scales and other features that allow a better assessment and management of pain [11,13,15,17,19]; 2 (10.5%) implemented evidence-based educational interventions, which include focus groups and application of guidelines with the professionals [18,20]; 2 (10.5%) applied cognitive-behavioral interventions, with a focus on understanding the nature of symptoms and improving the ability to control the symptoms [14,16]; and 1 (5.2%) applied daily pain management journals [12]. Table 2 highlights the main outcomes related to the studies included in the review.…”
Section: Health Education (N=10)mentioning
confidence: 99%
“…Education has been shown to improve attitudes about pain. 43 Finally, education is important in improving health care professional knowledge and opioids, which opioids to prescribe, and co-analgesics that can improve overall comfort. Pain management is both an art and a science and requires specific education.…”
Section: Tamperingmentioning
confidence: 99%